Familia disfuncional y autolesión en los adolescentes de la Unidad Educativa “Amelia Gallegos Díaz” - Orozco Barahona, Nataly Elizabeth (2021)
The research named “Dysfunctional Family and Self-injury in the Adolescents of the “Amelia Gallegos Díaz” school”, was developed with the objective of determining the relationship between dysfunctional family and self-injury variables. The method of study used was the descriptive method, it was correlational and cross-sectional; the population chosen was made up by the students of the “Amelia Gallegos Díaz” school, that belong to 8th, 9th and 10th grades of the upper basic section, totaling one hundred sixty-nine (169) students and the sample was non-probabilistic and intentional. The techniques and instruments applied were: The Self-Injury Satisfaction survey and the Family Functioning Evaluation questionnaire, with the collection and gathering of data, it was possible to carry out the observation and interpretation of the results. Finally, after the analysis, it was concluded that there is a relationship between dysfunctional families and self-injury in students, since the biggest problem revealed in the tests for committing self-injurious practices in adolescents of the educational institution are family problems, demonstrating the characteristics of dysfunctional families.